Perspektif Simbolik dan Proses Adaptasi Mahasiswa UNNES Terhadap Perbedaan Budaya Etika Kesopanan - Mutiatus Sholeha; Suci Anjani; Vidyambara Satyasih Wijaya; Devi Sekar Ramadhani; Muhammad Saputra Agung Pratama; Didi Pramono (Pusat Riset dan Inovasi Nasional, 2024)
This article aims to explore the main concepts in symbolic interactionism according to George Herbert Mead, and apply them in the context of UNNES students' adaptation to cultural differences in ethics and politeness ethics. This article was written using a qualitative method by describing the phenomenon in depth. The research data was obtained from interviews with several students from various regions with diverse cultures. The data collection was also carried out through secondary sources in the form of literature review. From data taken from several informants, the thing that is an obstacle for students from outside UNNES, especially outside Central Java, is adapting to or understanding the language used in everyday life. Through a better understanding of these dynamics, it is hoped that more effective strategies can be found to create an educational environment that is inclusive and supportive of students from different cultural backgrounds.